KEWIRAUSAHAAN DAN PENYUSUNAN PEMBUKUAN SEDERHANA DI KECAMATAN SUKMAJAYA (DEPOK) - Lily Suhaily; Sinta Boentoro; Petrus Ridaryanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
In Indonesia most men who work outside the home to make a living, while most women / housewives are only at home to take care of children and husbands. With mediocre economic conditions, housewives should work to increase family finances. If family finances are adequate, children can be sent to college, therefore the later successful children can increase their parents' dignity and improve the country's economy. In connection with this, in Sukmajaya Depok District there are still many housewives who do not have a side job therefore there is no income to increase their family finances. To be able to work outside the home, these housewives want to increase the knowledge of skills that can provide additional household income. One simple skill that may be given to housewives is the skill of cutting hair. The method of activity used in community service is a training method for housewives in Tirtajaya Village Hall, Sukmajaya Subdistrict, Depok. Community service activities in the form of training were held for 1 day, on May 17, 2017, pk. 12.00 to 15.00 at Tirtajaya Depok Village Hall. As many as forty housewives enthusiastically participated in training from start to finish. At the end of this training, The evaluation was conducted where participants were asked to fill out questionnaires related to the training provided. The survey results showed that most housewives expressed satisfaction with the training provided and would follow what was obtained in the training that had been given by speakers from FEB Unika Atma Jaya.